(untitled) - UNESCO (France, 2005)
The EFA Global Monitoring Report 2006 aims to shine a stronger policy spotlight on the more neglected goal of literacy - a foundation not only for achieving EFA but, more broadly, for reaching the overarching goal of reducing human poverty.
Keywords: Education and state,Education,Giáo dục và nhà nước,Giáo dục